The trouble with Kings : the composition of the book of Kings in the Deuteronomistic history - McKenzie, Steven L., 1953- (Vetus Testamentum, Supplements, 1991)
This book investigates the composition of the book of Kings and its implications for the Deuteronomistic History ( DH ) of which it is a part. McKenzie analyses Kings on the basis of Noth's model of a single author/editor behind the original DH . He contends that the Deuteronomist ( Dtr ) wrote the series of oracles against the Northern royal houses without utilizing a prior, running prophetic document that some scholars have posited behind Samuel and Kings. He regards many other prophetic stories in Kings, including most of the Elijah and Elisha legends as later additions to the DH , in accord with Noth's recognition that the original DH was frequently supplemented by various writers. McKenzie illustrates Dtr 's compositional techniques in a treatment of the accounts of Hezekiah and Josiah in Kings. He tentatively dates Dtr to Josiah's reign but believes that tensions among the many later additions to the work, including the report from Josiah's death on, suggest that they are not the result of systematic editing (e.g., Dtr 2). The book offers the most up-to-date survey of research on the DH and the most recent detailed analysis of the lengthy variant version of Jeroboam's reign in LXXB at 1 Kings 12:24a-z. It offers a fresh perspective on the original shape of the DH based on recent scholarship and the author's own critical investigation.